(untitled) (Prilozi za orijentalnu filologiju, 2017)
The muafiyet institution (mu’āfiyet) is one of the most important components in the process of development of Ottoman-type towns - kasabas - and of the movement of people into those towns. The urban population-related muafiyet reflected in the fact that the overall urban population was exempted from the raya status and therefore from the basic raya tax – resm-i çift. The official document by which the Sultan granted this benefit was the muafnama (mu’āfnāma). The muafnama confirmed full or partial exemption of the raya class from all or some of ordinary or extraordinary state or feudal levies. A note in the 1604 Comprehensive Bosnian Sanjak Census reads that ”the population of Banja Luka City is exempted from paying avariz-i divanije (imperial extraordinary taxes) and tekalif-i orfije (customary taxes) since with their weapons, body and soul they defend the Sultan’s lands and fortresses from damage which could be inflicted by an enemy”; in the future they will also be exempted from the said levies ”as long as they are ready to repulse with weapons the attacks of infidels against the Sultan’s lands and fortresses”. In the same census we can see that in Banja Luka this benefit applied equally both to Muslims and non-Muslims. Actually, 18 zimmijas - non-Muslims - registered in the town of Banja Luka”do not pay miller’s toll as they do not possess any arable land. They are not raya, they are craftsmen. They were not levied any taxes until a new census”. Banja Luka was granted the muafnama and was officially proclaimed atown – a kasaba– and its population was exempted from ordinary and extraordinary state and feudal taxes only after the first beylerbey of the Bosnian Eyalet, Ferhad-pasha, and the Banja Luka qadi had sent a request to the Porte. As a reply, the muafnama- the Sultan’s decree dated 26 Ramadan 996 AH /19 August 1588 AD came from Istanbul. The original transcript of the Banja Luka muafnama is kept under number 117 in the Oriental Collection of the Croatian Academy of Arts and Sciences in Zagreb.